Makna Doa Menurut Para Rasul Dan Implementasinya Terhadap Badan Pelaksana Harian Sinode GERMITA Di Kabupaten Kepulauan Talaud - Edwin Aldrin Essing; Sintje Abram; Marde C.S. Mawikere (Jurnal Ilmiah Wahana Pendidikan, 2021)
This paper aims to remind and see the role of church servants, especially the daily executor of the GERMITA synod to carry out the obligations instilled by the Lord Jesus Christ regarding prayer. Prayer is a spiritual relationship with the creator where we communicate with God. Prayer is a must that must be done to strengthen our faith, both in any situation. Because people who live without praying are like living without God, and in the end relying on their own strength, and will look like unbelievers who do not believe in God. The GERMITA congregation is a congregation that grows based on religious culture, so praying is a serious thing to remind the congregation to strengthen each other's faith.